A FRET-guided, NIR-responsive bubble-generating liposomal system for in vivo targeted therapy with spatially and temporally precise controlled release. (July 2016) - Chuang, Er-Yuan; Lin, Chia-Chen; Chen, Ko-Jie; Wan, De-Hui; Lin, Kun-Ju; Ho, Yi-Cheng; Lin, Po-Yen; Sung, Hsing-Wen
Abstract: The nonspecific distribution of therapeutic agents and nontargeted heating commonly produce undesirable side effects during cancer treatment since the optimal timing of triggering the carrier systems is unknown. This work proposes a multifunctional liposomal system that can intracellularly and simultaneously deliver the therapeutic drug doxorubicin (DOX), heat, and a bubble-generating agent (ammonium bicarbonate, ABC) into targeted tumor cells to have a cytotoxic effect. Gold nanocages that are encapsulated in liposomes effectively convert near-infrared light irradiation into localized heat, which causes the decomposition of ABC and generates CO2 bubbles, rapidly triggering the release of DOX. Additionally, a hybridized Mucin-1 aptamer is conjugated on the surface of the test liposomes, which then function as a recognition probe to enhance the uptake of those liposomes by cells, and as a molecular beacon to signal when the internalized particles have been maximized, which is the optimal time for photothermally triggering the release of the drug following the systemic administration of the liposomes. Empirical results reveal that this combined treatment effectively controls targeted drug release in a spatially and temporally precise fashion and so significantly increases the potency of the drug while minimizing unwanted side effects, making it a promising treatment for cancer.